Evaluación técnico-financiera de la implementación de la perforación con revestimiento y perforación con presión controlada para la disminución de tiempos de perforación en un pozo exploratorio (2018)
The present investigation consists in the compilation of technical and financial information concerning the techniques mentioned above. Selection and compilation of previous cases of application of Drilling with Coating and Drilling with Controlled Pressure as well as previous drilling project carried out by Canacol Energy LTD. Colombia in the block of interest, later performing the technical analysis of the feasibility of Drilling with Coating and Drilling with Controlled Pressure taking into account data obtained from case studies, the technical context referring to them in the country and subsequently making the comparison of These are through the use of the Technical Limit matrix of Canacol Energy LTD. Colombia, with the previous conventional drilling projects, the estimate of a planned well and the estimate of an ideal well. After the technical evaluation process, the financial evaluation of the method that presents the best result is performed, comparing the costs of this with the costs of a conventional drilling project using the financial variable known as Uniform Annual Cost Equivalent; finally it concludes on these results.